Устройство для подъема и перемещения отработавших тепловыделяющих сборок - Гаврилов П. М. Петр Михайлович; Ревенко Ю. А. Юрий Александрович; Бараков Б. Н. Борис Николаевич; Федосов Ю. Г. Юрий Георгиевич; Гамза Ю. В. Юрий Вячеславович
опубл. 10.05.11